Evaluasi Sistem Akuntansi Penjualan, Piutang, dan Penerimaan Kas pada PT Livio Furniture - Wicaksono, Aries (Binus Business Review, 2012)
Sales functions, receivables and cash receipts, are very important within the company. Sales function is a function which becomes the prime mover in revenues and earnings yields target. Therefore, the effectiveness and efficiency in the sales process, accounts receivable, and cash receipts become very important concern for company. To assess the effectiveness and efficiency of the functions of sales, accounts receivable, and cash receipts should be evaluated. The evaluation was conducted both in terms of procedures, policies, and implementation of the functions of sales, accounts receivable, and cash receipts. Evaluation was done by using the instrument in the form of a questionnaire and analyzing the procedures and policies that exist in PT Livio Furniture. The results of the evaluation of the functions of sales, accounts receivable, and cash receipts obtained the conclusion that internal controls at PT Livio Furniture is good enough and adequate, although still found that become a concern for the company.